Pengaruh Brand Image dan Brand Trust terhadap Brand Loyalty pada PT Bank Sinarmas - Sem Christina Hawila Sibagariang; Tinjung Desy Nursanti (The Winners, 2010)
Competition in the banking sector in Indonesia is getting more and more fierceevery day. PT Bank Sinarmas is a rapidly growing bank that continues to increase for the last 3 years. PT Bank Sinarmas committed to maintain this position. Therefore, they need to provide excellent service and deliver good quality savings products to build customer loyalty. The purpose of this study was to determine whether brand image (X1) and brand trust (X2) are partially influencing brand loyalty (Y), and to determine whether both brand image (X1) and brand trust (X2) are simultaneously influencing brand loyalty (Y). The analysis method used is multiple regression analysis using SPSS. Data is obtained through direct survey by distributing questionnaires to 100 clients of the bank at the main branch. The results indicates that the company's brand image significantly influences brand loyalty with R2 = 15.4% with regression equation Y = 1.962 +0.336 X1. Brand trust significantly influences brand loyalty with R2 = 17%, with regression equation Y = 1.838 +0.382 X2. While simultaneously, brand image and brand trust significantly influence brand loyalty, with R2 = 26.4% which form the regression equation Y = 1.281 +0.269 X1 + .315 X2. Thus, PT Bank Sinarmas needs to increase its brand image since a good image might become the company's competitive edge in creating loyalty, and subsequently loyalty will increase profitability.